(untitled) (Research, Society and Development, 2021)
The act of supplying a balanced diet to domestic cats and dogs contributes to promote a good life quality. Thus, it is necessary that the peculiarities of each species are considered, such as alimentary behavior and the characteristics of the gastrointestinal tract, since cats and dogs have many differences and particularities regarding the utilization and exploitation of many nutrients. In this sense, a thorough analysis concerning the individual conditions of the dog or cat before the dietary recommendations is essential. So, the goal of this review is to report the importance of the main nutrients related with the diets of domestic dogs and cats, as well as their role in the different life stages of these animals, from the search of books and scientific articles relevant to the subject in digital databases. Beyond the distinctions referring to nutrients within the diet, there are also particularities regarding the biological cycle of pets, in a way that it’s necessary to offer more attention to the peculiarities of animals inserted in reproductive, senile or growing stages. Along with these considerations, the analysis related to alternative diets in the feeding system of domestic dogs and cats is also an important variable concerning animal nutrition, in order to ensure the ingestion of an adequate quantity of each nutrient. Thus, the provision of a balanced diet is a crucial point in the process of guaranteeing health throughout the life cycle of cats and dogs.